Effect of corn replacement with cassava shaving flour in commercial laying hen diets - Cruz, Frank George Guimarães; Pereira Filho, Manoel; Lima Chaves, Francisco Alberto de (Revista Brasileira de Zootecnia, 2006)
The economic and productive performances of the dietary corn replacement with cassava shavings flour were evaluated in 200 Lohmann LSL laying hens with 46 weeks old, kept in 25 cages. The experiment was analyzed as a complete randomized design with five treatments and five replicates of eight birds per experimental unit. The treatments consisted of five levels (0, 25, 50, 75, and 100%) of corn replacement with cassava shavings flour. Quadractic effect on daily feed intake, with averages of 100.68, 101.00, 100.72, 99.42, and 99.50 g, in the respective replacement levels, was observed. Viability, egg production and feeding conversion (kg/dz and g/g) showed no significant differences. It was observed treatment effect (quadractic effect) on egg weight, albumen percentage, shell percentage, shell thickness and specific gravity. Egg mass and yolk percentage were not affected by the treatments. The 50% level treatment provided the lowest shell percentage in spite of presenting the highest egg weight. The egg yolk colour was affected by the treaments and showed linear decrease (7.84, 7.52, 7.35, 5.32, and 5.12) as the corn replacement level increased. From an economical viewpoint, the 100% level treatment presented higher difference on the cost per kilogram of feed, egg-dozen, and egg-box in relation to the other treatments. It is possible to replace up to 100% of corn by with cassava shavings flours with no changes on egg yield and feeding conversion. However, the replacement will depend on the relative cost of corn and pigments to be used for correcting egg yolk pigmentation. © 2006 Sociedade Brasileira de Zootecnia.
Efeito da substituição do milho pela farinha da apara de mandioca em rações para poedeiras comerciais
Keywords: Aves; Manihot Esculenta; Zea Mays